Asymmetric synthesis of functionalized benzo[a]quinolizine derivatives via a diastereoselective N-acyliminium ion cyclization - Lee, YS; Kang, SS; Choi, JH; Park, H (PERGAMON-ELSEVIER SCIENCE LTD, 1997)
A chiral synthesis of functionalized benzo[a]quinolizine derivative (5) has been accomplished starting from a chiral lactone 7. The key feature is the efficient control of the stereochemistry of ring juncture of the functionalized benzo[a]quinolizine derivative 5 by the N-acyliminium ion cyclization of chiral lactam 11b. (C) 1997 Elsevier Science Ltd.